PEER SUPPORT GROUP DALAM MENINGKATKAN KUALITAS HIDUP PENDERITA SKIZOFRENIA - Ratna Juwita Dewa Ayu Putu (STIKES ADVAITA MEDIKA TABANAN, 2022)
Peer support group therapy has been emphasis as a comprehensive method for improving the quality of life (QoL) in schizophrenia. WHO recommendation of these rehabilitative care collaborating with curative, promotif and their supporting system to achieve the goal of quality of life on fisic, psychis, social, and environtment. This was a pre-post test study in one group schizophrenia in Rumah Berdaya, Denpasar. This group was intervented with peer support group module for 3 months by the medical doctor. The QoL was assessed with the WHOQOL-BREF and analyzed using compare mean t-test. A total fourty schizophrenia which are fully cooperative completed the modules. Most of them is over 41 years old (57.14%), high educated 70.73%, single (82.93%), living with their core family (92.68%) and 23.44 ± 6.384 years old in onset. The mean scored of QoL was 70.57 (good QoL) ranged betwen 51.75-95.25 before the modules and 75.024 (good QoL) ranged between 47,00-100. This study showed that there was a significant difference of QoL before and after the modules completed (p0.00). This study proved that peer support group intervention in schizophrenia was significantly increased the mean of QoL score.